Clinical role of serum Copeptin in acute coronary syndrome - Manal Abd El Baky Mahmoud (The Egyptian Heart Journal, 2018)
Objective: To assess the role of Copeptin in diagnosis of acute myocardial infarction in troponin-blind period. Subjects and methods: This study was conducted on 40 patients who presented to emergency department complaining of chest pain and were highly suspicious to have acute cardiac ischemia, in addition to 10 subjects serving as a healthy control group. Blood samples were collected for determination of CK-MB, cTnI and Copeptin. These were measured twice (in patients’ group); at 3 h and then at 6–9 h from admission time. Results: The first sample revealed a non-significant difference between UA group and AMI group as regards CKMB and troponin, however, high significant difference was found as regards Copeptin (Z = 5.29, P < 0.001). Moreover, ROC curve analysis of serum Copeptin for discriminating AMI group from UA group in the first sample showed diagnostic sensitivity and specificity of 100%. In conclusion: Determination of copeptin in early diagnosis of AMI has diagnostic value being superior to a conventional cTn-I within the first three hours after acute chest pain. Keywords: Copeptin, Acute coronary syndrome